Aberrant N-glycolylneuraminic acid in breast MCF-7 cancer cells and cancer stem cells - Yang, Wenqian; Jiang, Yuan; Guo, Qulian; Tian, Zhixin; Cheng, Zhigang (Frontiers in Molecular Biosciences, 2022)
N-glycolylneuraminic acid (Neu5Gc) normally does not appear in human because of lack of the hydroxylase enzyme that converts cytidine-5′-monophosphate-N-acetylneuraminic acid (CMP-Neu5Ac) to CMP-Neu5Gc; yet Neu5Gc has been observed in human cancer cells and tissues, and antibodies against Neu5Gc have been detected in healthy humans which are obstacles for clinical xenotransplantation and stem cell therapies. Study of Neu5Gc in human is thus of important pathological and clinical relevance. Here we report the N-glycoproteomics characterization of aberrant Neu5Gc in breast MCF-7 cancer cells and cancer stem cells (CSCs) at the molecular level of intact N-glycopeptides, where comprehensive information (peptide backbones, N-glycosites, N-glycan monosaccharide compositions and linkage structures) were reported. The results are an important addition to previous Neu5Ac data, and the method can be extended to characterization of other biological and clinical systems with Neu5Gc.